Prediction of a region with high transmission (reflectance) for bandpass interferential filters by using the method of pointer function - Yaremchuk, Ya.; Fitio, V.M.; Bobitski, Ya.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The analysis of transmission spectrums of periodical multilayer interference
thin-films systems is carried out. Spectral dependences of pointer function from
wavelength for interference bandpass filters are obtained. These dependences allow to
prognostic of regions of high transmission or reflectance for different periodical
multilayer systems.